Moral Distress in the Pediatric Intensive Care Unit: An Italian Study - Sannino, Patrizio; Giannì, Maria Lorella; Carini, Micaela; Madeo, Mario; Lusignani, Maura; Bezze, Elena; Marchisio, Paola; Mosca, Fabio (Frontiers in Pediatrics, 2019)
Introduction: There is paucity of data within the Italian context regarding moral distress in intensive pediatric settings. The aim of the present study was to assess the frequency, intensity, and level of moral distress experienced by nurses working in a sample of pediatric intensive care units (PICUs). Materials and Methods: A cross-sectional questionnaire survey was conducted in eight PICUs from five northern Italian regions in a convenience sample of 136 nurses. Moral distress was evaluated using the modified Italian version of the Moral Distress Scale Neonatal–Pediatric Version (MDSNPV). Each item was scored in terms of frequency and intensity on a five-point Likert scale, ranging from 0 to 4. The total frequency and intensity scores for all the 21 clinical items were comprised between 0 and 84. For each item, the level of moral distress was derived by multiplying the frequency score by the intensity score and quantified with a score ranging from 0 to 16. The total score of the moral distress level for the 21 items ranged from 0 to 336. Results: The mean total scores for the frequency, intensity and level of moral distress were 24.1 ± 10.4, 36.2 ± 18.6, and 57.7 ± 37.1, respectively. The clinical situations identified as the major causes of moral distress among nurses in the present study involved end-of-life care and resuscitation. At multivariate logistic regression analysis, number of deaths occurring in PICUs, having children and intention to leave work due to moral distress resulted to be independently associated with a higher total moral distress level. Conclusions: The results of the present study contribute to the understanding of moral distress experience in acute pediatric care settings, including the clinical situations associated with a higher moral distress level, and highlight the importance of sharing thoughts, feelings and information within the multidisciplinary health care professional team for effective shared decision making, particularly in situations involving end-of-life care and resuscitation.